EU security practices in Eastern Europe: Extending European peace or managing risks? - Mădălina Dobrescu (Europa-Kolleg Hamburg, Institute for European Integration, 2015)
This paper captures the contradictions at the heart of the European Union's (EU) security approach in Eastern Europe and reveals their implications in practice. The EU's security approach towards the states at its Eastern borders has been characterized by pervasive ambiguity, oscillating between inclusiveness and a normative/duty narrative and a securitizing perspective that advances a threat/risk narrative. Caught between these diverging narratives and the practices they inspire, the EU's policy instruments struggle to achieve their goals and make positive impact on the ground. The paper takes as a casestudy one of the EU's iconic policy instruments in Eastern Europe, the EU Border Assistance Mission to Moldova and Ukraine (EUBAM). The mission's attempts to act both according to a normative/duty and a threat/risk narrative have resulted in EUBAM undermining its own efforts and can be expected to generate negative consequences for peace and stability in the region. The paper concludes that the one lesson that the EU must draw form these past experiences is that it needs to mainstream conflict resolution principles in all its policies towards countries affected by conflicts. The Union's engagement with the countries of the Eastern Partnership is carried out through a myriad of different policies and an even more complex web of policy tools. Understanding what the implications of these various instruments for the conflict settlement prospects in the region are would ensure that the EU makes the best use of its resources and avoids contradictory policies.
Keywords: 320; European Union; security; Eastern Partnership; civilian missions; conflict resolution